Business, the state and economic policy : the case of Italy - Amyot, Grant; Amyot, Grant (London : Routledge, 2004)
The book compares Italy with the US, Germany, and Japan while exploring the influence of economic realities, organized interests, and political institutions on the formation of policy in Italy. This interesting, readable and important book gives the reader an insight into the sources and workings of power in a major advanced industrial state. It will be appreciated by students and researchers with an interest in European politics, political theory, and political economy. It will also be a good tool for policy-makers and professionals with an interest in Italian business, economics and politics.
Includes bibliographical references (p. [189]-206) and index.
rpm 03/05/13
Loans
Keywords: Capitalism; Economic policy; Italian capitalism; Italy